Analysis of mathematical problem-solving processes of Islamic religious education students on zakat material with low numeracy literacy - Chintia Putri Wulandari; Lovi Leoni; Elya Yudiasfira; Shahzadi Hina Sain (UNION : Jurnal Ilmiah Pendidikan Matematika, 2026)
This study examines the mathematical problem-solving processes of Islamic Religious Education (IRE) students in solving zakat-related problems from the perspective of low numeracy literacy. Numeracy literacy is essential because it enables students to interpret quantitative information and apply mathematical reasoning in religious contexts such as zakat, which requires both conceptual understanding and accurate calculation. However, many IRE students experience difficulties in solving zakat problems, particularly at low levels of numeracy literacy. This research employed a descriptive qualitative design involving 29 IRE students, one of whom, a student with low numeracy literacy, was selected for in-depth analysis. Data were collected through written tests, observations, and semi-structured interviews, and analyzed through data reduction, data display, and conclusion drawing, with triangulation applied across the data sources. The findings reveal that students with low numeracy literacy tend to approach problems mechanically by directly applying the 2.5% zakat rule without adequately understanding the context, interpreting data, or constructing appropriate mathematical models. Their problem-solving processes show weaknesses across all stages, including limited planning, inaccurate modeling, and a lack of evaluation and reflection. These results indicate that low numeracy literacy affects not only the accuracy of solutions but also the overall thinking process. Therefore, integrating mathematical modeling, structured problem-solving stages, and reflective evaluation in zakat instruction is essential for fostering meaningful and contextual learning. This study contributes a process-oriented account of how low numeracy literacy constrains contextual interpretation, mathematical modeling, and reflective evaluation in zakat problem solving, thereby providing an empirical basis for integrating numeracy development into religious education.